THE CONCEPT OF THE LITERARY AND ARTISTIC DISCOURSE IN MODERN LINGUISTICS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, it is substantiated the importance and relevance of the study of discourse in general and literary- and- artistic discourse  in particularly, theoretical issues of understanding the concept of literary and artistic discourse in modern science and  highlighted, an overview  of various scientific concepts in the field of the study of discourse.